2015
DOI: 10.1371/journal.pbio.1002093
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bipartite Centrosome Coordinates the Apicomplexan Cell Cycle

Abstract: Apicomplexan parasites can change fundamental features of cell division during their life cycles, suspending cytokinesis when needed and changing proliferative scale in different hosts and tissues. The structural and molecular basis for this remarkable cell cycle flexibility is not fully understood, although the centrosome serves a key role in determining when and how much replication will occur. Here we describe the discovery of multiple replicating core complexes with distinct protein composition and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
413
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(447 citation statements)
references
References 66 publications
33
413
1
Order By: Relevance
“…This has drawn the attention to a pivotal role for the centrosome in coordinating the mitotic, karyokinetic and cytokinetic events (34, 48, 49, 139). The centrosome resides near the spindle pole embedded in the nuclear envelope.…”
Section: Parasite Replicationmentioning
confidence: 99%
“…This has drawn the attention to a pivotal role for the centrosome in coordinating the mitotic, karyokinetic and cytokinetic events (34, 48, 49, 139). The centrosome resides near the spindle pole embedded in the nuclear envelope.…”
Section: Parasite Replicationmentioning
confidence: 99%
“…However, the mechanistic coordination of these two events remains largely unclear. In an elegant recent study, Suvorova and colleagues systematically searched for orthologs of known centrosomal proteins in Toxoplasma and used these reagents to evaluate the phenotypes of previously isolated temperature sensitive cell division cycle mutants [4]. Localization studies with the candidate centrosomal proteins led to the surprising discovery of two different core structures making up the parasite's centrosome.…”
mentioning
confidence: 99%
“…Since the physical connection of inner core and the centrocone (spindle pole) remains intact in a TgSfi1-deficient background, this finding suggests a mitosis organizing function for the inner core, but, moreover, illustrates that the cores can function independently, and that it is possible to uncouple budding from mitosis. In a reciprocal experiment, Chen and Gubbels showed that in a TgCep250-deficient inner core line, the budding cycle persists but mitosis is disrupted [4]. These observations suggest that the different cores likely associate with different functions of the centrosome, i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…gondii also possesses CenH3, suggesting that conventional kinetochores are a conserved feature in apicomplexans [84] (Fig 2). TgCenH3 associates with centromeres, which cluster together at the centrocone, a unique, specialised spindle pole body that constitutively associates with the nuclear envelope throughout the cell cycle [8486]. …”
Section: Introductionmentioning
confidence: 99%